2007
DOI: 10.1007/s10689-007-9166-4
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cancer and the FAMMM syndrome

Abstract: Hereditary cancer syndromes provide excellent models for molecular genetic studies that may aid significantly in case detection, surveillance, and management. Ultimately, molecularly based designer pharmaceuticals may emerge from this research, such as the case of trastuzumab (Herceptin) in HER-2/neu positive breast cancer, and imatinib (Gleevec) in chronic myelocytic leukemia and gastrointestinal stromal tumors. Importantly, these molecular findings may fuel significant clues to cancer control. This backgroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(70 citation statements)
references
References 47 publications
0
69
0
1
Order By: Relevance
“…This disorder involves mutations in the p16 gene or CDNK2 gene which also can lead to pancreatic cancer. The risk of pancreatic cancer development by the age of 75 has been reported to be between 17 and 25% [26,27]. In some studies, there has been reported to be a 13-to 22-fold increase of pancreatic cancer [27].…”
Section: Gene (S) Involved Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…This disorder involves mutations in the p16 gene or CDNK2 gene which also can lead to pancreatic cancer. The risk of pancreatic cancer development by the age of 75 has been reported to be between 17 and 25% [26,27]. In some studies, there has been reported to be a 13-to 22-fold increase of pancreatic cancer [27].…”
Section: Gene (S) Involved Clinical Featuresmentioning
confidence: 99%
“…The risk of pancreatic cancer development by the age of 75 has been reported to be between 17 and 25% [26,27]. In some studies, there has been reported to be a 13-to 22-fold increase of pancreatic cancer [27]. CDKN2A is a tumor suppressor involved in inducing cell cycle arrest in the G1 and G2 phase.…”
Section: Gene (S) Involved Clinical Featuresmentioning
confidence: 99%
“…Familial atypical mole-multiple melanoma (FAMMM) is an autosomal dominant disease associated with mutations within CDKN2A gene (p16 Leiden) [45,46] . Its inactivation is associated with PDAC that was found 13 to 38-fold more frequent than expected [46,47] , with a cumulative risk Lami G et al .…”
Section: Familial Atypical Mole-multiple Melanomamentioning
confidence: 99%
“…The incidence of melanoma is increased, and a family history of melanoma and pancreatic cancer should be sought. 32 In addition to the increased risk of pancreatic cancer (estimated to be as high as 22-fold) in affected families, reports have linked this family cancer syndrome to an increased risk of breast cancer. 33,34 What's new Melanoma/pancreatic cancer syndrome appears to be related to a mutation of the gene encoding cyclindependent kinase inhibitor-2A (CDKN2A) on chromosome 9p21.…”
Section: Descriptionmentioning
confidence: 99%
“…Endoscopic retrograde cholangiopancreatography and endoscopic ultrasound are sensitive screening tests for pancreatic cancer. 32 Genetic counseling is mandatory for patients with the melanoma/pancreatic cancer syndrome.…”
Section: Descriptionmentioning
confidence: 99%